2018
DOI: 10.1136/bmj.k211
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of a childhood obesity prevention programme delivered through schools, targeting 6 and 7 year olds: cluster randomised controlled trial (WAVES study)

Abstract: ObjectiveTo assess the effectiveness of a school and family based healthy lifestyle programme (WAVES intervention) compared with usual practice, in preventing childhood obesity.DesignCluster randomised controlled trial.SettingUK primary schools from the West Midlands.Participants200 schools were randomly selected from all state run primary schools within 35 miles of the study centre (n=980), oversampling those with high minority ethnic populations. These schools were randomly ordered and sequentially invited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
127
3
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(148 citation statements)
references
References 33 publications
7
127
3
11
Order By: Relevance
“…Our results demonstrate that males accumulate higher overall levels of TEE and PAEE than females across all ages, a finding that is consistent with other British cohort studies investigating energy expenditure with objective methods [31][32][33][34] This finding highlights the role that absolute body size plays in the accumulation of absolute energy expenditure, but also underlines obesity's inverse association with physical activity energy expenditure. This relationship was apparent regardless of the measure of obesity and of the measure of physical activity, with those with higher absolute bodyfat levels and those in the highest FMI category accumulating less physical activity than slimmer counterparts.…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrate that males accumulate higher overall levels of TEE and PAEE than females across all ages, a finding that is consistent with other British cohort studies investigating energy expenditure with objective methods [31][32][33][34] This finding highlights the role that absolute body size plays in the accumulation of absolute energy expenditure, but also underlines obesity's inverse association with physical activity energy expenditure. This relationship was apparent regardless of the measure of obesity and of the measure of physical activity, with those with higher absolute bodyfat levels and those in the highest FMI category accumulating less physical activity than slimmer counterparts.…”
Section: Discussionsupporting
confidence: 92%
“…This might seem logical as treatments tend to be given to those children who are already overweight and 'have more to lose'. Quite in line with our results, a recent evaluation of a comprehensive school-based and familybased obesity prevention program delivered through schools in the UK (112) found no significant effects regarding weight or physical activity. Their conclusion that interventions delivered through schools alone are not enough and that the wider societal context including the media and food industry need to take responsibility for childhood obesity is something the meta-synthesis presented here echoes.…”
Section: Discussionsupporting
confidence: 91%
“…A pivotal meta-analysis highlighted that PA interventions dedicated to improving quantity of PA report little effect [15]. More recently, Adab et al [16] reported in a longitudinal study that a one-year school/community-based PA intervention had no effect on body mass index (BMI) z-scores at 15-or 30-months post-intervention, highlighting that communities and schools are unlikely to impact on the childhood obesity epidemic by incorporating only PA targeted interventions.…”
Section: Introductionmentioning
confidence: 99%